2018
DOI: 10.3390/su10061995
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Approach to Artificial and Natural Green Walls According to Ecological Sustainability

Abstract: Abstract:Together with the rapid industrialization of the world, urbanization is also uncontrollably increasing. Such an increase in urbanization exerts the greatest pressure on natural resources, obligating people to live in intense structural spaces and increasing the need for green spaces in cities. Because of the expensive costs of horizontal surfaces being "green", urban places are faced with serious green-infrastructure problems. In recent years, alternatives have been searched for to eliminate such defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 11 publications
3
17
0
1
Order By: Relevance
“…"A cost-benefit analysis of the green wall case indicates that this measure is economically promising when valuing the noise attenuation in the quieter area and adding the amenity/aesthetic value of the green wall" [90] (p. 3770). Cost analysis by Meral et al [82] confirms that living walls are the most expensive type of man-made VGS. "Considering the costs of two wall systems, it was observed that a green facade could be established with about 12.01 of the cost of living walls" [82] (p. 14).…”
Section: Economic Benefits and Installation Costsmentioning
confidence: 99%
See 3 more Smart Citations
“…"A cost-benefit analysis of the green wall case indicates that this measure is economically promising when valuing the noise attenuation in the quieter area and adding the amenity/aesthetic value of the green wall" [90] (p. 3770). Cost analysis by Meral et al [82] confirms that living walls are the most expensive type of man-made VGS. "Considering the costs of two wall systems, it was observed that a green facade could be established with about 12.01 of the cost of living walls" [82] (p. 14).…”
Section: Economic Benefits and Installation Costsmentioning
confidence: 99%
“…Cost analysis by Meral et al [82] confirms that living walls are the most expensive type of man-made VGS. "Considering the costs of two wall systems, it was observed that a green facade could be established with about 12.01 of the cost of living walls" [82] (p. 14). A cost-benefit analysis of the living walls showed that "they have a longer payback period of 17 years considering the local unsubsidized electricity rates in UAE" [91] (p. 8).…”
Section: Economic Benefits and Installation Costsmentioning
confidence: 99%
See 2 more Smart Citations
“…In solving this problem, "green construction" can be considered as promising technologies for reducing ecological footprint due to CO 2 sequestration by additional biomass (trunk, branches, bark, leaves, roots) and a substrate. One of the effective low carbon technologies are the "green structures" (Alperen Meral et al, 2018), (Chen et al, 2018), (Qin et al, 2018), (Jian-feng et al, 2010), (Kristin et al, 2009), (Kuronuma et al, 2018), (Margareth et al, 2018), (Mayrand and Clergeau, 2018), (Sanderman and Amundson, 2009), (Tuttolomondo et al, 2018), (Yanling et al, 2014). They can improve the quality of air in cities as well as reduce the emission of greenhouse gases.…”
Section: Introductionmentioning
confidence: 99%